2011
DOI: 10.1121/1.3652869
|View full text |Cite
|
Sign up to set email alerts
|

Random focusing of nonlinear acoustic N-waves in fully developed turbulence: Laboratory scale experiment

Abstract: A laboratory experiment was conducted to study the propagation of short duration (25 μs) and high amplitude (1000 Pa) acoustic N-waves in turbulent flow. Turbulent flows with a root-mean-square value of the fluctuating velocity up to 4 m/s were generated using a bidimensional nozzle (140 × 1600 mm(2)). Energy spectra of velocity fluctuations were measured and found in good agreement with the modified von Kármán spectrum for fully developed turbulence. Spherical N-waves were generated by an electric spark sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…This definition of the rise time, which corresponds to the steepest region of the front, was recently proposed from laboratory-scale sonic boom studies to characterize shock structures of sparkgenerated pulses propagating in air. 46,47 The definition is equivalent to the classical definition (time needed for the pressure at the shock of the amplitude A s to increase from 0.1ÁA s to 0.9ÁA s ) for shocks governed by the stationary solution of the Burgers equation: 48…”
Section: B Measurement Protocols and Pulse Definitionsmentioning
confidence: 99%
“…This definition of the rise time, which corresponds to the steepest region of the front, was recently proposed from laboratory-scale sonic boom studies to characterize shock structures of sparkgenerated pulses propagating in air. 46,47 The definition is equivalent to the classical definition (time needed for the pressure at the shock of the amplitude A s to increase from 0.1ÁA s to 0.9ÁA s ) for shocks governed by the stationary solution of the Burgers equation: 48…”
Section: B Measurement Protocols and Pulse Definitionsmentioning
confidence: 99%
“…1). 6 The repetition rate of the pulses was 1 Hz; the wavefront was assumed to have a spherical geometry. Acoustic pulses introduced variations of air density and, as a result, variations of the optical refractive index which are schematically shown in Fig.…”
Section: A Experimental Arrangement For Optical Measurementsmentioning
confidence: 99%
“…In the laboratory-scale experiments which simulate the N-shaped waveform, a front and tail shock waves have the same waveform deformed by turbulent effects [10,30]. It seems that the front and tail shock waves receive the same shock focusing/diffracting effects.…”
Section: Turbulence Interaction With Long Rise-time Signaturementioning
confidence: 99%
“…Salze et al [29] showed a shock propagation distance relates to a transverse shock focusing region and experimentally estimated its shock focal region. Averiyanov et al [28,30] showed that an overpressure decrease and the arrival time are governed by the large scale of a velocity fluctuation, and the small scales of a velocity fluctuation mainly cause increasing the rise time. In the typical model experiments [10,29,30], in order to simulate the N-shaped sonic boom propagation in the real atmosphere, the characteristic length scales, such as a wavelength, a turbulent interaction distance, and the geometrical turbulence length scales, were adjusted.…”
Section: Introductionmentioning
confidence: 99%